Streamrate stagnation-point flow of a nanofluid on a stationary cylinder - Amerian, Vahid; Mohammadiun, Hamid; Mohammadiun, Mohammad; Khazaee, Iman (International Journal of Scientific World, 2015)
The steady-state, viscous flow of Nanofluid in the vicinity of an axisymmetric stagnation point of a stationary cylinder is investigated. The impinging free-stream is steady and with a constant strain rate . Exact solution of the Navier–Stokes equations is derived in this problem. A reduction of these equations is obtained by use of appropriate transformations introduced in this research. The general self-similar solution is obtained when the wall temperature of the cylinder is constant. All the solutions above are presented for Reynolds numbers ranging from 0.1 to 1000 and selected values of particle. For all Reynolds numbers, as the particle fraction increases, the depth of diffusion of the fluid velocity field in radial direction, the depth of the diffusion of the fluid velocity field in -direction, shear-stresses and pressure function decreases.